Intervention improves restaurant employees' food safety compliance rates - Pilling, Valerie K.; Brannon, Laura A.; Shanklin, Carol W.; Roberts, Kevin R.; Barrett, Betsy B.; Howells, Amber D. (My University, 2009)
Abstract: Purpose – This paper aims to evaluate the relative effectiveness of four-hour ServSafe® food safety training, a theory-based intervention targeting food service employees' perceived barriers to implementing food safety practices, and a combination of the two treatments. Dependent measures include behavioral compliance with and perceptions of control over performing hand washing, use of thermometers, and handling of work surfaces. Design/methodology/approach – Four groups are compared: employees receiving only ServSafe® training, intervention alone, training and intervention, and no treatment. Employees complete a questionnaire assessing perceived barriers to practicing the targeted behaviors. Then, employees are observed in the production area for behavioral compliance. Findings – Training or intervention alone is better than no treatment, but the training/intervention combination is most effective at improving employees' compliance with and perceptions of control over performing the behaviors. Research limitations/implications – Research is limited to restaurant employees in three states within the USA, in only 31 of the 1,298 restaurants originally contacted. Future research should identify barriers of other types of food service employees and evaluate the effectiveness of these and other intervention strategies. Practical implications – ServSafe® training can be enhanced with a simple intervention targeting food service employees' perceived barriers to food safety. Providing knowledge and addressing barriers are both important steps to improving food safety in restaurants. Originality/value – No previous research has used the theory of planned behavior to develop an intervention targeting food service employees' perceived barriers to implementing food safety practices. Research also has not attempted to improve the effectiveness of ServSafe® food safety training by adding an intervention.
Keywords: Food safety; Barriers; Intervention; Food safety training; ServSafe; Food handling